Factors determining weight gain in adults and relation with glucose tolerance. (25th March 2013) - Soriguer, Federico; Rojo‐Martínez, Gemma; Valdés, Sergio; Tapia, Maria José; Botas, Patricia; Morcillo, Sonsoles; Delgado, Elías; Esteva, Isabel; Ruiz de Adana, Maria Soledad; Almaraz, María Cruz; Diaz‐Cadorniga, Francisco; Gutierrez‐Repiso, Carolina; et al.
Summary Objective Modifications in lifestyle, diet and certain clinical events are major contributors for the high prevalence of obesity. The aim of this study was to assess factors associated with weight gain in a population of Spanish adults. Design The study was undertaken in two population‐based cohorts from the north and the south of Spain (baseline and after 6 years). The Asturias Study, in the north, included 1034 persons aged 30–75 years, of whom 701 were reassessed. The Pizarra Study, in the south, included 1226 persons aged 18–65 years, of whom 783 were re‐evaluated. Both studies involved a nutritional questionnaire, a physical examination and an oral glucose tolerance test (OGTT). Results During the follow‐up, 32·3% of the participants lost weight, 34·5% gained fewer than 4 kg and 33·2% gained more than 4 kg. Weight gain was greater in persons younger than 50 years and in those with an initial body mass index below 30. Weight gain was associated with a greater incidence of type 2 diabetes mellitus (T2DM) and abnormal glucose tolerance, whereas weight loss in persons with these disorders was associated with a normal OGTT 6 years later. Persons who took less exercise and those who reported a higher daily calorie intake experienced greater weight gain. Conclusion The longitudinal changes in weight affect the development of T2DM and abnormal glucose tolerance. The weight is a dynamic phenomenon affected by several social customs.